2015
DOI: 10.4187/respcare.03984
|View full text |Cite
|
Sign up to set email alerts
|

Plan to Have No Unplanned: A Collaborative, Hospital-Based Quality-Improvement Project to Reduce the Rate of Unplanned Extubations in the Pediatric ICU

Abstract: BACKGROUND: Although under-reported and understudied, unplanned extubations carry a significant risk of patient harm and even death. They are an important yardstick of quality control of care of intubated patients in the ICU. A unit-based risk assessment and multidisciplinary approach is required to decrease the incidence of unplanned extubations. METHODS: As part of a qualityimprovement initiative of Children's Hospital at Montefiore, all planned and unplanned extubations in a multidisciplinary 20-bed pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…This increase can be attributed to the hospital's having moved some experienced critical care nurses to support a newly set-up branch hospital, which decreased the quality of care in the ICU of our hospital's main branch ICU. Other studies [5,1618] report similar findings in different populations. Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This increase can be attributed to the hospital's having moved some experienced critical care nurses to support a newly set-up branch hospital, which decreased the quality of care in the ICU of our hospital's main branch ICU. Other studies [5,1618] report similar findings in different populations. Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU.…”
Section: Discussionsupporting
confidence: 73%
“…Fontanez-Nieves et al [16] reported a significant reduction of UE from 16.1 to 4.5/100 ventilator-days in neonates using the methods with 3 PDCA cycles over 20 months; Tripathi et al [5] reported a reduction in a pediatric ICU (PICU) from 3.55 to 2.59/100 intubation days after implementing a patient care policy targeting the risk factors, followed by extensive nursing and other personnel education over 12 months; Merkel et al [17] found a significant decrease in 3 years in the rate of UE in a neonatal intensive care unit (NICU) after bundles of potentially better practices had been implemented following sequential PDSA cycles; and Rachman and Mink [18] also reported that the effect of the quality improvement program to reduce UE had been successfully maintained even 9 years after implementation in the PICU. In summary, our findings and those of other studies [5,1618] indicate that a multidisciplinary quality improvement program can effectively reduce UE in the ICU, and the effect can be maintained and even improved 15 years after the sequential introduction of different interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Tripathi et al 1 recently published in RESPI-RATORY CARE assessing the impact of a quality-improvement project on the incidence of unplanned extubations. By carrying out this quality-improvement project, they were able to decrease the rate of unplanned extubations from 3.55 to 2.59 per 100 intubation days.…”
Section: To the Editormentioning
confidence: 93%
“…After the implementation of their qualityimprovement program, the rate of unplanned extubations/100 intubation days dropped from 3.55 to 2.59. Tripathi et al 1 have not provided the statistical significance of this improvement. It is noteworthy to highlight that compared with contemporary qualityimprovement studies with 50 -80% improvement, 3,4,6 a 27% improvement in the unplanned extubation rate is disappointing, since the final unplanned extubation rate remained higher than in other contemporary studies (range: 0.29 -1.5/100 intubation days) 3,4,[6][7][8][9] and also higher than the benchmark reported as acceptable in the literature (Ͻ1/100 intubation days).…”
Section: To the Editormentioning
confidence: 99%
“…5 There are several quality improvement studies in pediatric and adult populations when using different interventions, which showed decreased unplanned extubation rates in the hospital. [6][7][8][9][10] Despite these studies, no interventions have been shown consistently to be effective in preventing unplanned extubations, which remains a significant hospital-acquired condition with high health-care cost. 11,12 There are a wide variety of endotracheal tubes (ETT) available from different manufacturers, such as tubes with a suction port above the cuff or silver-impregnated tubes to decrease the colonization of the ETT.…”
Section: Introductionmentioning
confidence: 99%